2022
DOI: 10.1002/ese3.1120
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic double‐Gaussian analytical wake model for an isolated horizontal‐axis wind turbine

Abstract: An anisotropic double Gaussian (DG) model for analytical wake modeling to predict the streamwise wake velocity behind an isolated non-yawed horizontal-axis wind turbine is proposed. The proposed model is based upon the conservation of mass and momentum inside a streamtube control volume. The wake growth rate parameters to distinguish the wake expansion rate between lateral and vertical directions were tuned based on numerical and measurement data of utility-scale turbines. It was found that the proposed model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…This advantage was confirmed using computational fluid dynamics (CFD) data, where the root mean square error results showed the superiority of the DG model against the SG model for lateral velocity deficit predictions within a full‐wake region 30 . Most recently, the anisotropic DG model was compared with the anisotropic SG model referring to large eddy simulation (LES) and lidar data 37 . The results showed that the anisotropic DG model could perform better than the anisotropic SG model within the full‐wake region, thus reconfirming the effectiveness of the DG‐based wake model.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…This advantage was confirmed using computational fluid dynamics (CFD) data, where the root mean square error results showed the superiority of the DG model against the SG model for lateral velocity deficit predictions within a full‐wake region 30 . Most recently, the anisotropic DG model was compared with the anisotropic SG model referring to large eddy simulation (LES) and lidar data 37 . The results showed that the anisotropic DG model could perform better than the anisotropic SG model within the full‐wake region, thus reconfirming the effectiveness of the DG‐based wake model.…”
Section: Introductionmentioning
confidence: 84%
“…Based on turbine micro‐siting practices, the HAWTs within a wind farm are rarely installed over 11 D for the interrow spacing 37 . Within this spacing distance, it was observed both experimentally 26 and numerically 14,27 that the single HAWT wakes expanded linearly under different turbine operating and inflow conditions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations